Emerging and reemerging human fungal pathogens that affect people with weakened immune systems: a systematic review - Genet, Amere; Girma, Abayeneh (Universa Medicina, 2024)
BACKGROUNDEmerging and reemerging human fungal pathogens are becoming more closely associated with morbidity and mortality, with 13 million infections and 1.5 million deaths per year. They are most often associated with critically ill and immunosuppressed patients. Therefore, this systematic review focused on emerging and reemerging human fungal pathogens that affect immunosuppressed individuals. METHODS A systematic literature search was performed using PubMed, ScienceDirect, Web of Science, Google Scholar, and other sources (Google engine and manual search using a reference list). The data were extracted in a structured format prepared using Microsoft Excel. RESULTSCryptococcus neoformans, Candida auris, Aspergillus fumigatus, Candida albicans, Nakaseomyces glabrata (Candida glabrata), Histoplasma spp., Mucorales (Rhizopus spp., Mucor spp., Lichtheimia spp., and others), Fusarium spp., Candida tropicalis, Candida parapsilosis, Pichia kudriavzevii (Candida krusei), Talaromyces marneffei and Pneumocystis jirovecii were emerging and reemerging fungal pathogens reported among critically ill and immunocompromised patients including but not limited to HIV patients and patients with infectious diseases such as influenza, COVID-19, and tuberculosis as well as chronic conditions or co-morbidities such as asthma, hepatic cirrhosis, cancer, diabetes, cystic fibrosis (CF), transplant recipients, and chronic obstructive pulmonary disease (COPD). Climate change, agricultural activities, occupational hazards, deforestation, migratory trends of people, soil dispersion, decreased immunity of patients, biofilm development, medication tolerance, and resistance to antifungal therapies are all factors that contribute to the emergence of fungal diseases. CONCLUSIONThis review makes recommendations for policymakers, public health experts, and other stakeholders to improve the response to these fungal infections, including laboratory capacity and surveillance, fostering sustainable research and innovation, implementing public health initiatives, and limiting the development of antifungal drug resistance.